Wrapping Paper from a Mixture of Hardwoods from Himachal Pradesh - Guha, S. R. D.; Mathur, G. M.; Sharma, Y. K.; Karira, B. G. (Indian Forester, 1970)
Laboratory and pilot plant scale trials on the suitability of mixture of hardwoods for wrapping papers from the Northern Zone of India surveyed by the Pre-investment Survey of Forest Resources are described. The results indicate that this mixture requires some admixture of long fibre for smooth running of the machine.